Cool sunscreen yarn and manufacturing method thereof
By combining surface-treated sheet-like or strip-shaped zinc oxide particles with light polyamide or polyethylene fibers, a cool sunscreen yarn with excellent thermal conductivity is prepared, which solves the problem of poor thermal conductivity of existing yarns and achieves efficient human heat dissipation and antibacterial properties.
Patent Information
- Application Number
- CN202411764742.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-04
AI Technical Summary
The existing cool yarns cannot meet the needs of use due to poor thermal conductivity, poor processing performance, poor dyeing performance and poor heat dissipation of human bodies.
Flake-like or strip-like zinc oxide particles are used as thermal conductivity materials and surface treatment is carried out to improve the binding force with fiber materials. Combined with light polyamide or polyethylene fibers, cool sunscreen yarns with excellent thermal conductivity are prepared through melt spinning process.
It realizes efficient heat conduction of yarn, improves the heat dissipation effect of human heat, and has excellent antibacterial properties and lower machine wear, enhancing the production stability of yarn.
Smart Images

Figure CN119553383A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of textiles, in particular to a cool sun-proof yarn and a manufacturing method thereof. Background Art
[0002] At present, most of the common cooling yarns on the market use jade powder, mica powder, aluminum oxide, magnesium oxide, boron nitride and other high thermal conductivity materials as cooling particles, which are added to the fiber to improve the thermal conductivity of the fiber or fabric, thereby achieving a cooling effect. However, in actual production and processing, most of the existing cooling materials are irregular particles with sizes ranging from tens of nanometers to several microns. When mixed with fiber materials, many particles are too small and irregular in shape, and are affected by contact thermal resistance and interface thermal resistance. Not only can they not form an efficient thermal conduction path in the material, but they may also hinder thermal conductivity and reduce the cooling effect of the yarn.
[0003] In addition, materials such as jade powder, mica, and aluminum oxide have high hardness and are easy to wear precision equipment and workpieces, resulting in reduced product yield. These materials are also difficult to color, which limits their addition amount and is not conducive to effective performance improvement. At the same time, materials such as aluminum oxide, magnesium oxide, and boron nitride have strong absorption and warming effects on infrared radiation, forming an internal circulation of heat energy between the fabric and human skin, which is not conducive to the loss of heat from the human body. It can be seen that ordinary cool yarn cannot meet the use requirements.
[0004] The above problems are worth solving. Summary of the invention
[0005] In order to overcome the deficiencies of the prior art, the present invention provides a cool sun-screen yarn and a manufacturing method thereof.
[0006] The technical solution of the present invention is as follows:
[0007] A method for manufacturing a cool sun-proof yarn, comprising the following steps:
[0008] S1. Zinc oxide particles are selected as the thermal conductive material, and the shape of the zinc oxide particles is flake and / or strip; the thickness of the flake zinc oxide is not less than 100 nanometers, the diameter D50 of the flake zinc oxide is greater than or equal to 500 nanometers and less than or equal to 1000 nanometers, and the diameter D97 of the flake zinc oxide does not exceed 5000 nanometers; the diameter of the strip zinc oxide is greater than or equal to 100 nanometers and less than 300 nanometers, the length D50 of the strip zinc oxide is greater than or equal to 500 nanometers and less than or equal to 1000 nanometers, and the length D97 of the strip zinc oxide does not exceed 5000 nanometers;
[0009] S2. Surface treatment of the zinc oxide particles is performed so that the zinc oxide particles can be closely combined with the fiber material to reduce the contact thermal resistance between the materials;
[0010] S3, selecting shiny polyamide or polyethylene as the fiber material, mixing it with zinc oxide particles, and preparing a masterbatch containing zinc oxide;
[0011] S4. The prepared masterbatch is mixed with shiny polyamide chips or polyethylene chips, and the yarn is obtained by melt spinning.
[0012] As a preferred technical solution of the present invention, the surface treatment of zinc oxide particles comprises the following steps:
[0013] S201, dissolving γ-aminopropyltriethoxysilane in acetone, wherein the mass of γ-aminopropyltriethoxysilane is 1% of the mass of zinc oxide;
[0014] S202, adding zinc oxide particles and stirring at high speed;
[0015] The high-speed stirring time is 5 minutes to ensure that the surface of the zinc oxide particles fully contacts and adsorbs γ-aminopropyltriethoxysilane;
[0016] S203, heating to 100°C and reacting for a period of time;
[0017] The reaction time is 4 hours, so that γ-aminopropyltriethoxysilane is chemically bonded to the surface of zinc oxide;
[0018] S204, filtering and separating the zinc oxide particles, and washing them with anhydrous ethanol;
[0019] The number of rinses is 2 times to fully remove excess unreacted substances;
[0020] S205, vacuum drying at 100°C;
[0021] The vacuum drying time is more than 4 hours to completely remove moisture and solvent to obtain surface-treated zinc oxide particles.
[0022] Further, in step 201, the step of dissolving γ-aminopropyltriethoxysilane in acetone, wherein the mass of γ-aminopropyltriethoxysilane is 1% of the mass of zinc oxide, comprises the following steps:
[0023] Step A, weighing the mass of the zinc oxide particles to be treated;
[0024] Step B, calculating the required mass of γ-aminopropyltriethoxysilane according to the ratio of 1%;
[0025] Step C: dissolving the calculated γ-aminopropyltriethoxysilane in an appropriate amount of acetone to form a solution.
[0026] As a preferred technical solution of the present invention, the specific steps of preparing the masterbatch are as follows:
[0027] S301, drying the shiny polyamide slice or polyethylene slice in a vacuum environment at 80-100° C.;
[0028] S302, grinding the fiber slices into powder;
[0029] S303, mixing the sliced powder with the surface treated zinc oxide particles, adding 3% of a solvent-free system dispersant, and stirring and mixing thoroughly;
[0030] S304, extruding and granulating the mixed material to obtain a masterbatch.
[0031] Furthermore, in step 301, the shiny polyamide slice or polyethylene slice is dried in a vacuum environment at 80-100° C., specifically, the steps are as follows:
[0032] The polyamide slices were dried in a vacuum environment at 100°C for 4 hours, or the polyethylene slices were dried in a vacuum environment at 80°C for 2 hours.
[0033] Furthermore, in step 304, the mixed material is extruded and granulated, and the specific steps are as follows:
[0034] The mixture of masterbatch and polyamide chips is extruded and granulated at 280°C by a twin-screw extruder; or the mixture of masterbatch and polyethylene chips is extruded and granulated at 220°C by a twin-screw extruder.
[0035] As a preferred technical solution of the present invention, the melt spinning is a two-component chrysanthemum petal core process, and the steps are:
[0036] The spinneret adopts a multi-hole spinneret to produce multi-daisy-petal core-shaped fibers. The two feed ports of the bicomponent spinning machine are respectively fed with fiber slices with different masterbatch contents, one of which is a fiber slice with a masterbatch addition of 10-30%, and the other is a fiber slice with a masterbatch addition of 0-10%;
[0037] The two-component spinning unit is started, and the two fiber slices are melted and then spun into yarn through a porous daisy-petal core spinneret. The two fiber materials are spaced apart in the circumferential direction of the single fiber of the yarn, so that the cross section of the fiber is distributed in a daisy-petal core shape, and several daisy petals with high-content masterbatch are connected at the yarn core.
[0038] The present invention also provides a cool sun-proof yarn, which is made by the manufacturing method of the cool sun-proof yarn as described in the above scheme, and the melt spinning is preferably a two-component chrysanthemum petal core process, and the number of chrysanthemum petals is 8-24 petals.
[0039] As a preferred technical solution of the present invention, the cool sun-protection yarn includes a yarn body, a plurality of first chrysanthemum petal areas and a plurality of second chrysanthemum petal areas are arranged at intervals along the circumference of the yarn body, a yarn central axis area is arranged in the center of the yarn body, and a plurality of the second chrysanthemum petal areas are connected through the yarn central axis area.
[0040] The present invention according to the above scheme has the following beneficial effects:
[0041] The present invention effectively solves the problems of poor thermal conductivity, poor processing performance, poor dyeing performance and poor heat dissipation effect of human body in existing cool yarns by optimizing the morphology and processing technology of cool particles; specifically, in the selection of thermal conductive materials, flaky or strip-shaped zinc oxide particles are selected, and the thickness and size of the zinc oxide particles are strictly controlled to ensure that an effective heat conduction channel is formed in the fiber, and finally the prepared cool masterbatch containing zinc oxide is mixed with glossy PE or PA6 for melt spinning to obtain a cool yarn with good thermal conductivity, which can effectively conduct human body heat to the surface of the fabric for heat dissipation; in particular, the chrysanthemum petal core-shaped fiber yarn obtained by the double-component chrysanthemum petal core process in the melt spinning process can not only achieve the maximum addition ratio of zinc oxide and improve the heat conduction effect, but also achieve the transverse and longitudinal two-way heat conduction effect;
[0042] Furthermore, the size of the flaky or strip-shaped zinc oxide particles is concentrated between 500-1000nm, and has strong sunlight reflection performance, achieving the effect of heat shielding and sun protection;
[0043] Furthermore, the flaky or strip-shaped zinc oxide particles have excellent absorption effect on ultraviolet rays, and the fabrics made of them can block ultraviolet rays;
[0044] Furthermore, the sheet or strip zinc oxide particles, PA or PE materials are low-absorption materials for human body heat radiation, which is conducive to the direct heat exchange between human body heat radiation and the external environment through the yarn, thereby achieving efficient heat dissipation of the human body;
[0045] Furthermore, there are a large number of nanoparticle materials in the flaky or strip-shaped zinc oxide particles, and these nanomaterials can inhibit or kill microorganisms such as bacteria, viruses or fungi, giving the yarn excellent antibacterial properties;
[0046] Furthermore, the flake or strip zinc oxide particles have a lower hardness, which reduces the wear of the machine and improves the stability of yarn production. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 It is a schematic diagram of the method flow of the present invention;
[0048] Figure 2 This is a schematic diagram of the yarn structure obtained in Example 2 of the present invention;
[0049] Figure 3 Schematic diagram of heat conduction of chrysanthemum-shaped yarn;
[0050] Figure 4 This is a microscopic image of flaky zinc oxide particles;
[0051] Figure 5 This is a microscopic image of strip-shaped zinc oxide particles;
[0052] Figure 6 This is a microscopic image of irregular zinc oxide particles;
[0053] Figure 7 This is a microscopic image of spherical nano zinc oxide particles;
[0054] Figure 8 Schematic diagram of a 9-hole spinneret used to make 16-petal core fibers.
[0055] In the figure,
[0056] 1. The first chrysanthemum petal area; 2. The second chrysanthemum petal area DETAILED DESCRIPTION
[0057] In order to better understand the purpose, technical scheme and technical effect of the present invention, the present invention is further explained in conjunction with the accompanying drawings and embodiments. It should be noted that similar numbers and letters represent similar items in the following drawings. Therefore, once an item is defined in one drawing, it does not need to be further defined and explained in the subsequent drawings. At the same time, it is stated that the embodiments described below are only used to explain the present invention and are not used to limit the present invention.
[0058] It should be noted that the indicated orientation or position relationship is based on the orientation or position relationship shown in the drawings, or is the orientation or position relationship in which the application product is usually placed when used, or is the orientation or position relationship commonly understood by technical personnel in this field, or is the orientation or position relationship in which the application product is usually placed when used. It is only for the convenience of describing the present application and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application.
[0059] The terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features. "Several" means two or more, unless otherwise clearly and specifically defined.
[0060] Embodiment 1
[0061] like Figure 1 , Figure 4 As shown, a method for making a cool sun-proof yarn comprises the following steps:
[0062] Step 1: Select flaky zinc oxide particles as thermal conductive material. The thickness of the flaky zinc oxide is 100 nanometers. The shape of the zinc oxide is a circular flake. The diameter D50 of the flaky zinc oxide in the selected material is 834 nanometers, and the diameter D97 of the flaky zinc oxide is 4.192 micrometers.
[0063] In other optional embodiments, the thickness of the flaky zinc oxide is equal to 110nm, 120nm, 130nm, 140nm, or 150nm, etc. The diameter D50 of the flaky zinc oxide in the selected material is 500nm, 600nm, 700nm, 800nm, 900nm or 1000nm, etc., and the diameter D97 of the flaky zinc oxide is 4000nm, 4100nm, 4200nm, 4300nm, 4400nm, 4500nm, 4600nm, 4700nm, 4800nm, 4900nm or 5000nm, etc.
[0064] Step 2: Surface treatment of the flaky zinc oxide particles is performed. The treatment process is to dissolve γ-aminopropyltriethoxysilane accounting for 1% of the mass of zinc oxide in acetone, and then add the flaky zinc oxide particles so that the zinc oxide particles can be closely combined with the fiber material to reduce the contact thermal resistance between the materials. The specific steps are:
[0065] S201, dissolving γ-aminopropyltriethoxysilane in acetone, wherein the mass of γ-aminopropyltriethoxysilane is 1% of the mass of zinc oxide;
[0066] Step 201 includes the following specific steps:
[0067] Step A, weighing the mass of the zinc oxide particles to be treated;
[0068] Step B, calculating the required mass of γ-aminopropyltriethoxysilane according to the ratio of 1%;
[0069] Step C: dissolving the calculated γ-aminopropyltriethoxysilane in an appropriate amount of acetone to form a solution.
[0070] S202, adding zinc oxide particles and stirring at high speed for 5 minutes to ensure that the surface of the zinc oxide particles is fully in contact with and adsorbs γ-aminopropyltriethoxysilane;
[0071] S203, heating to 100° C. and reacting for 4 hours to allow γ-aminopropyltriethoxysilane to chemically bond with the surface of zinc oxide;
[0072] S204, filtering and separating the zinc oxide particles, and washing them twice with anhydrous ethanol to fully remove excess unreacted substances;
[0073] S205, vacuum drying at 100° C. for more than 4 hours to completely remove moisture and solvent to obtain surface-treated flaky zinc oxide particles.
[0074] In other optional embodiments, the mass of γ-aminopropyltriethoxysilane is 1.5%, 2.0%, 2.5% or 3.0% of the mass of zinc oxide. In step 202, high-speed stirring is 6 minutes, 7 minutes, 8 minutes or 10 minutes. In step 203, the heating temperature is 110°C, 120°C, 95°C or 90°C, and the reaction time is 3.5 hours, 4.5 hours or 5 hours. In step 204, the number of rinses with anhydrous ethanol is 3 times, 4 times or 5 times. In step 205, the vacuum environment temperature is 90°C, 95°C, 110°C or 120°C, and the drying time is 4.5 hours, 5 hours or 6 hours.
[0075] Step 3: Select shiny polyamide as the fiber material, mix it with zinc oxide particles, and prepare a masterbatch containing zinc oxide. The polyamide is preferably polyamide 6 (PA6). The specific steps are:
[0076] S301, drying the glossy polyamide 6 slices in a vacuum environment at 100° C. for 4 hours;
[0077] S302, using a pulverizer to fully grind the polyamide 6 slices into powder;
[0078] S303, adding the surface treated zinc oxide particles, mixing with the polyamide 6 chip powder, adding 3% of the total mass of a solvent-free system dispersant, and stirring and mixing thoroughly;
[0079] S304, extruding and granulating the mixed material at about 280° C. using a twin-screw extruder to obtain a refrigeration masterbatch having a cool feeling.
[0080] Step 4: Mix the masterbatch prepared in step 3 with the glossy polyamide 6 chips, and melt-spin to obtain yarn. The melt spinning is a blending process, and the specific steps are: mix the masterbatch and the polyamide 6 chips in a mass ratio of 7:93 and then melt-spin. The obtained yarn specification can be a fully drawn yarn with a linear density of 70 deniers and composed of 36 monofilaments.
[0081] In other optional embodiments, the mass ratio of the masterbatch to the polyamide 6 chips can also be 6:94, 8:92, 9:91 or 10:90, etc.
[0082] It should be noted that the glossy mentioned in this embodiment includes highly glossy and semi-glossy, which are mainly used to describe the surface gloss characteristics of the fiber. Glossy means that the fiber has a higher surface gloss, and no matting agent, such as titanium dioxide, is added during the production process. Highly glossy is similar to glossy, emphasizing higher gloss; semi-gloss means that a small amount of matting agent is added during the production process, which reduces the gloss of the fiber surface, but still maintains a certain brightness. In contrast, matte or full matte means that more matting agent is added during the production process of the fiber, which makes the gloss of the fiber surface almost completely disappear, presenting a matte effect.
[0083] Embodiment 2
[0084] like Figure 2 and Figure 3 As shown, a method for making a cool sunscreen yarn, the method is the same as that of embodiment 1, comprising:
[0085] Step 1, selecting flaky zinc oxide particles as a thermal conductive material, the thickness of the flaky zinc oxide is equal to 100 nanometers, the shape of the zinc oxide is a circular flake, the diameter D50 of the flaky zinc oxide in the selected material is 834 nanometers, and the diameter D97 of the flaky zinc oxide is 4.192 micrometers;
[0086] Step 2, surface treating the flaky zinc oxide particles, wherein the treatment process is to dissolve γ-aminopropyltriethoxysilane accounting for 1% of the weight of zinc oxide in acetone, and then add the flaky zinc oxide particles;
[0087] Step 3, selecting shiny polyamide 6 as the fiber material, mixing it with zinc oxide particles, and preparing a masterbatch containing zinc oxide;
[0088] Step 4: Mix the masterbatch prepared in step 3 with the glossy polyamide 6 chips, and obtain the yarn after melt spinning.
[0089] The difference is that the spinning process in step 4 is a two-component chrysanthemum petal core process, and the specific steps are: using a two-component spinning unit, the spinneret uses a 9-hole spinneret, refer to Figure 8 , make 16-daisy-petal core-shaped fibers, the two feed ports of the two-component spinning machine are respectively fed with fiber slices with different masterbatch contents, the feed port of the 9-hole spinneret is for fiber slices with a masterbatch addition of 30%, and the other is for fiber slices with a masterbatch addition of 6%; start the two-component spinning unit, and after the two fiber slices are melted, they are spun into yarn through a porous daisy-petal core spinneret. The two fiber materials are spaced apart in the circumferential direction of the single fiber of the yarn, so that the cross-section of the yarn fiber is distributed in the shape of daisy-petals, and several daisy petals with masterbatch added are connected at the fiber core.
[0090] In this embodiment, the cross section of the yarn fiber has 16 petals, including 8 first petals and 8 second petals, the first petals are made of polyamide 6 slices with a masterbatch addition of 30%, and the second petals are made of polyamide 6 slices with a masterbatch addition of 6%, the first petals and the second petals are distributed at intervals, and several first petals are connected at the core of the cross section of the yarn fiber. The yarn specification is a fully drawn yarn with a linear density of 70 deniers and composed of 36 monofilaments.
[0091] In other optional embodiments, the two-component chrysanthemum petal core process can also use a 7-hole spinneret to produce 12-petal core fibers, a 10-hole spinneret to produce 18-petal core fibers, and other multi-hole spinnerets to produce more petal core fibers.
[0092] The cool sunscreen yarn made by the manufacturing method of the cool sunscreen yarn of this embodiment includes a yarn body, a plurality of first chrysanthemum petal areas 1 and a plurality of second chrysanthemum petal areas 2 are arranged at intervals along the circumference of the fibers in the yarn body, a yarn central axis area is arranged at the center of the fibers in the yarn body, and the plurality of second chrysanthemum petal areas 2 are connected by the yarn central axis area. The material of the first chrysanthemum petal area 1 is polyamide 6 with a masterbatch addition amount of 6%, and the material of the second chrysanthemum petal area 2 and the yarn central axis area is the same, both of which are polyamide 6 materials with a masterbatch addition amount of 30%.
[0093] Since the second chrysanthemum petal area 2 of the fiber in the yarn body is mixed with a masterbatch of high concentration zinc oxide, and the masterbatch addition amount reaches 30%, the thermal conductivity of the second chrysanthemum petal area 2 is relatively high. Since the chrysanthemum petals are connected by the core in the fiber, and the core is also added with 30% masterbatch, the core also has excellent heat conduction ability. Once a chrysanthemum petal contacts the heat source, it can be quickly conducted to each chrysanthemum petal. The two adjacent cool sunscreen fibers can transfer heat laterally to other fibers through the second chrysanthemum petal area 2 and the yarn center axis area; and the second chrysanthemum petal area 2 and the yarn center axis area of the yarn body fiber are distributed along the longitudinal direction of the fiber, and the heat can be transferred longitudinally through the second chrysanthemum petal area 2 and the yarn center axis area. Therefore, the cool sunscreen yarn of Example 2 is higher and faster in heat conduction efficiency than the cool sunscreen yarn of Example 1. In addition, the first daisy-petal area is a PA6 material with 6% masterbatch added. This low-added masterbatch material can ensure the strength of the fiber in the spinning process. While the overall high addition of masterbatch, it reduces the breakage of the yarn, allowing the spinning to proceed smoothly and achieve spinnable performance. In addition, PA6 or PE has a high penetration effect of human infrared, which can realize more efficient human infrared radiation to the external environment and achieve a rapid cooling effect.
[0094] Embodiment 3
[0095] A method for making a cool sunscreen yarn, the method is the same as that of the first embodiment, comprising: selecting zinc oxide particles as a thermal conductive material; performing surface treatment on the zinc oxide particles; preparing a masterbatch containing zinc oxide; mixing the masterbatch with shiny fiber slices, and obtaining the yarn after melt spinning, the difference being that: when preparing the masterbatch containing zinc oxide, shiny polyethylene is used as the fiber material; and the masterbatch is mixed with the shiny polyethylene slices, and the yarn is obtained after melt spinning.
[0096] Specifically, step 3A includes the following steps:
[0097] S3A01, dry the glossy polyethylene slices in a vacuum environment at 80°C for 2 hours;
[0098] S3A02, use a pulverizer to fully grind the polyethylene slices into powder;
[0099] S3A03, add the surface treated zinc oxide particles, mix with the polyethylene chip powder, add 3% of the total mass of solvent-free system dispersant, and stir and mix thoroughly;
[0100] S3A04, the above-mentioned mixed material is extruded and granulated at about 220°C using a twin-screw extruder to obtain a refrigeration masterbatch with a cool feeling.
[0101] The melt spinning in step 4A is a blending process, and the specific steps are: mixing the masterbatch and the polyethylene chips in a mass ratio of 7:93 and then melt spinning. The yarn specification obtained can be a fully drawn yarn with a linear density of 70 deniers and composed of 36 monofilaments.
[0102] Embodiment 4
[0103] like Figure 1 and Figure 5 As shown, a method for making a cool sun-proof yarn comprises the following steps:
[0104] Step 1: Select strip zinc oxide particles as thermal conductive material, the diameter of the strip zinc oxide is equal to 100 nanometers, the length D50 of the strip zinc oxide in the selected material is equal to 890 nanometers, and the length D97 of the strip zinc oxide is equal to 4110 nanometers.
[0105] In other optional embodiments, the diameter of the strip zinc oxide particles is equal to 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, 210nm, 220nm, 230nm, 240nm, 250nm, 260nm, 270nm, 280nm, 290nm, 300nm, etc. The length D50 of the strip zinc oxide in the selected material is equal to 500nm, 600nm, 700nm, 800nm, 900nm or 1000nm, etc., and the length D90 of the strip zinc oxide is equal to 1500nm, 2100nm, 2200nm, 2300nm, 2400nm, 2500nm, 2600nm, 2700nm, 2800nm, 2900nm or 3000nm, etc.
[0106] Step 2: Surface treatment of the strip-shaped zinc oxide particles.
[0107] Step 3: Select shiny polyamide as the fiber material, mix it with zinc oxide particles, and prepare a masterbatch containing zinc oxide. The polyamide is preferably polyamide 6 (PA6).
[0108] Step 4: Mix the masterbatch prepared in step 3 with the glossy polyamide 6 slices, and obtain yarn after melt spinning. The melt spinning is a blending process. The obtained yarn specification can be a fully drawn yarn with a linear density of 70 deniers and composed of 36 monofilaments.
[0109] The specific steps of step 2 to step 3 in this embodiment are consistent with those in embodiment 1 and are not described in detail here.
[0110] Embodiment 5
[0111] A method for making a cool sunscreen yarn, the method is the same as that of embodiment 4, comprising:
[0112] Step 1: Select strip zinc oxide particles as thermal conductive material, the diameter of the strip zinc oxide is equal to 100 nanometers, the length D50 of the strip zinc oxide in the selected material is equal to 890 nanometers, and the length D97 of the strip zinc oxide is equal to 4110 nanometers.
[0113] Step 2: Surface treatment of the strip-shaped zinc oxide particles.
[0114] Step 3: Select shiny polyamide as the fiber material, mix it with zinc oxide particles, and prepare a masterbatch containing zinc oxide. The polyamide is preferably polyamide 6 (PA6).
[0115] Step 4: Mix the masterbatch prepared in step 3 with the glossy polyamide 6 chips, and obtain the yarn after melt spinning.
[0116] The difference is that the melt spinning is a two-component chrysanthemum petal core process. The specific steps of the two-component chrysanthemum petal core process are consistent with those of Example 2 and are not repeated here. The yarn specification obtained can be a fully drawn yarn with a linear density of 70 deniers and composed of 36 monofilaments.
[0117] Embodiment 6
[0118] A method for making a cool sunscreen yarn, the method is the same as that of Example 4, except that: in step 3, shiny polyethylene is selected as the fiber material, and the masterbatch is mixed with the shiny polyethylene chips, and the yarn is obtained after melt spinning.
[0119] Specifically, step 3A includes the following steps:
[0120] S3A01, dry the glossy polyethylene slices in a vacuum environment at 80°C for 2 hours;
[0121] S3A02, use a pulverizer to fully grind the polyethylene slices into powder;
[0122] S3A03, add the surface treated zinc oxide particles, mix with the polyethylene chip powder, add 3% of the total mass of solvent-free system dispersant, and stir and mix thoroughly;
[0123] S3A04, the above-mentioned mixed material is extruded and granulated at about 220°C using a twin-screw extruder to obtain a refrigeration masterbatch with a cool feeling.
[0124] The melt spinning in step 4A is a blending process, and the specific steps are: mixing the masterbatch and the polyethylene chips in a mass ratio of 7:93 and then melt spinning. The yarn specification obtained can be a fully drawn yarn with a linear density of 70 deniers and composed of 36 monofilaments.
[0125] Embodiment 7
[0126] A method for making a cool sun-proof yarn, comprising the following steps:
[0127] Step 1: Select and mix flaky zinc oxide particles and strip-shaped zinc oxide particles as thermal conductive materials, wherein:
[0128] The thickness of the zinc oxide flakes is equal to 100 nanometers, and the shape of the zinc oxide is a circular flake. Among the selected materials, 50% of the zinc oxide particles have a diameter of 834 nanometers, and 97% of the zinc oxide particles have a diameter of 4.192 micrometers.
[0129] The diameter of the strip zinc oxide is equal to 100 nanometers, the length D50 of the strip zinc oxide in the selected material is equal to 890 nanometers, and the length D97 of the strip zinc oxide is equal to 4110 nanometers.
[0130] Step 2: Surface treatment is performed on the flaky zinc oxide particles and the strip-shaped zinc oxide particles.
[0131] Step 3: Select shiny polyamide as the fiber material, mix it with zinc oxide particles, and prepare a masterbatch containing zinc oxide. The polyamide is preferably polyamide 6 (PA6).
[0132] Step 4: Mix the masterbatch prepared in step 3 with the glossy polyamide 6 chips, and obtain the yarn after melt spinning.
[0133] The melt spinning is a blending process. The yarn specification obtained can be a fully drawn yarn with a linear density of 70 deniers and composed of 36 monofilaments.
[0134] The specific steps of step 2 to step 3 in this embodiment are consistent with those in embodiment 1 and are not described in detail here.
[0135] Embodiment 8
[0136] A method for making a cool sunscreen yarn, the method is the same as that in Example 7, a mixture of flaky zinc oxide particles and strip-shaped zinc oxide particles is selected as a heat conductive material, the difference being that the melt spinning is a two-component chrysanthemum petal core process, see the two-component chrysanthemum petal core process in Example 2 for details, which will not be described here. The yarn specification obtained is a fully drawn yarn with a linear density of 70 deniers and composed of 36 monofilaments.
[0137] The present invention also provides several comparative examples to demonstrate the thermal conductivity of the yarns prepared by the preparation method of the present invention.
[0138] Comparative Example 1
[0139] like Figure 6 As shown, a method for making a cool sun-proof yarn comprises the following steps:
[0140] Step 1: Select irregular zinc oxide particles as thermal conductive material, wherein the diameter D50 of the zinc oxide particles in the selected material is 858 nanometers and the diameter D97 is 4.45 micrometers.
[0141] Step 2: Select shiny polyamide 6 as the fiber material, mix it with zinc oxide particles, and prepare a masterbatch containing zinc oxide. This step is consistent with step 3 of embodiment 1, and will not be described here.
[0142] Step 3: The prepared masterbatch is mixed with the glossy polyamide 6 slices, and the yarn is obtained after melt spinning. The melt spinning is a blending process. This step is consistent with step 4 of embodiment 1 and will not be described in detail here.
[0143] Comparative Example 2
[0144] A method for making a cool sunscreen yarn, the method is the same as that of comparative example 1, except that the melt spinning in step 3 is a two-component chrysanthemum petal core process, see the two-component chrysanthemum petal core process in Example 2 for details, which will not be repeated here.
[0145] Comparative Example 3
[0146] A method for making a cool sun-proof yarn, comprising the following steps:
[0147] Step 1: Select irregular zinc oxide particles as thermal conductive material, wherein the diameter D50 of the zinc oxide particles in the selected material is 858 nanometers and the diameter D97 is 4.45 micrometers.
[0148] Step 2: Surface treatment of irregular zinc oxide particles.
[0149] Step 3: Select glossy polyamide 6 as the fiber material, mix it with zinc oxide particles, and prepare a masterbatch containing zinc oxide.
[0150] Step 4: Mix the masterbatch prepared in step 3 with the glossy polyamide 6 chips, and obtain the yarn after melt spinning.
[0151] The specific steps of step 2 to step 3 in this embodiment are consistent with those in embodiment 1 and are not described in detail here.
[0152] Comparative Example 4
[0153] A method for making a cool sunscreen yarn, the method is the same as that in Example 3, irregular zinc oxide particles are selected as the thermal conductive material, the difference is that the melt spinning is a two-component chrysanthemum petal core process, see the two-component chrysanthemum petal core process in Example 2 for details, which will not be repeated here.
[0154] Comparative Example 5
[0155] like Figure 7 As shown, a method for making a cool sun-proof yarn comprises the following steps:
[0156] Step 1: Select spherical nano zinc oxide particles as thermal conductive material, wherein the diameter D50 of the zinc oxide particles is 45 nanometers and the diameter D97 is 82 nanometers.
[0157] Step 2: Select shiny polyamide 6 as the fiber material, mix it with zinc oxide particles, and prepare a masterbatch containing zinc oxide. This step is consistent with step 3 of embodiment 1, and will not be described here.
[0158] Step 3: Mix the prepared masterbatch with the glossy polyamide 6 slices, and obtain the yarn after melt spinning. The melt spinning is a blending process. This step is consistent with step 4 of embodiment 1 and will not be described in detail here.
[0159] Comparative Example 6
[0160] A method for making a cool sunscreen yarn, the method is the same as that in Example 3, spherical nano zinc oxide is selected as the thermal conductive material, the difference is that the melt spinning is a two-component chrysanthemum petal core process, see the two-component chrysanthemum petal core process in Example 2 for details, which will not be repeated here.
[0161] Finally, the present invention performs thermal conductivity tests on the yarns in the above-mentioned embodiments 1 to 8 and comparative examples 1 to 5 according to ISO 2207-2:2022, and adds two polymer fiber yarns without zinc oxide, namely, PA6 without zinc oxide and PE without zinc oxide. The comparative test results are as follows:
[0162]
[0163]
[0164] Comparing the above tables, we can draw the following conclusions:
[0165] 1. By comparing PA6 without adding zinc oxide masterbatch with Examples 1, 2, 4, 5, 7, and 8, and with Comparative Examples 1 to 6, it can be seen that zinc oxide plays a role in improving the thermal conductivity of PA6 yarn; by comparing PE without adding zinc oxide masterbatch with Examples 3 and 6, it can be seen that zinc oxide also plays a role in improving the thermal conductivity of PE yarn.
[0166] 2. By comparing Example 1 with Comparative Example 1, Comparative Example 3, and Comparative Example 5, and by comparing Example 2 with Comparative Example 2, Comparative Example 4, and Comparative Example 6, it can be seen that: no matter the melt spinning adopts the blending process as in Example 1 or the two-component chrysanthemum petal core process as in Example 2, the surface-treated flaky zinc oxide has a better thermal conductivity effect than the irregular zinc oxide particles and the spherical nano zinc oxide particles.
[0167] 3. By comparing Example 4 with Comparative Example 1, Comparative Example 3, and Comparative Example 5, and by comparing Example 5 with Comparative Example 2, Comparative Example 4, and Comparative Example 6, it can be seen that: no matter the melt spinning adopts the blending process as in Example 4 or the two-component chrysanthemum petal core process as in Example 5, the surface-treated strip zinc oxide has a better thermal conductivity effect than the irregular zinc oxide particles and the spherical nano zinc oxide particles.
[0168] 4. By comparing Example 7 with Comparative Example 1, Comparative Example 3, and Comparative Example 5, and by comparing Example 8 with Comparative Example 2, Comparative Example 4, and Comparative Example 6, it can be seen that: whether the melt spinning adopts the blending process as in Example 7 or the two-component chrysanthemum petal core process as in Example 8, the surface-treated flaky zinc oxide and strip zinc oxide mixture have a better thermal conductivity effect than the irregular zinc oxide particles and the spherical nano zinc oxide particles.
[0169] 5. By comparing Example 7 with Example 1 and Example 4, and by comparing Example 8 with Example 2 and Example 5, it can be seen that whether the melt spinning adopts the blending process or the two-component chrysanthemum core process, the mixed use of flake zinc oxide and strip zinc oxide has a better heat conduction effect than the use of flake zinc oxide alone, or the use of strip zinc oxide alone.
[0170] 6. By comparing Example 2 with Example 1, Example 5 with Example 4, and Example 8 with Example 7, it can be seen that the melt spinning using the two-component chrysanthemum core process such as Examples 2, 5, and 8 has a better heat conduction effect than the melt spinning using the blending process such as Examples 1, 4, and 7.
[0171] 7. By comparing Example 3 with Example 1, and by comparing Example 6 with Example 4, it can be seen that the use of PE slices has a better heat conduction effect than the use of PA6 slices.
[0172] In summary, the cool sunscreen yarn prepared by the method of the present invention has the following advantages over ordinary yarn:
[0173] a. Zinc oxide particles have excellent ultraviolet absorption, so the yarn can have an excellent blocking effect on ultraviolet rays;
[0174] b. Since the fiber contains a large amount of zinc oxide particles, and the size of the particles is concentrated between 500-1000nm, it has strong reflection performance for sunlight and achieves the effect of heat shielding and sun protection;
[0175] c. The fiber has high thermal conductivity and can effectively transfer human body heat to the surface of the fabric for heat dissipation. In particular, the fiber yarn with a chrysanthemum petal core can not only achieve the maximum addition ratio of zinc oxide and improve the thermal conductivity, but also achieve high thermal conductivity in both the horizontal and vertical directions;
[0176] d. Zinc oxide particles and PA6 or PE materials have high penetration of human infrared, which can achieve more efficient human infrared radiation to the external environment and achieve rapid cooling effect;
[0177] e. Zinc oxide particles have excellent coloring properties and will not affect the coloring properties of the yarn in PA6;
[0178] f. The hardness of zinc oxide particles is low, which reduces the wear of the machine and improves the stability of yarn production;
[0179] g. Zinc oxide particles do not absorb water, especially when added to PA6 fibers in large proportions, it can reduce the fiber's moisture absorption capacity and improve the fiber's quick-drying properties;
[0180] h. There are a large number of nanoparticles in the flaky or strip-shaped zinc oxide particles, and these nanomaterials can inhibit or kill microorganisms such as bacteria, viruses or fungi, giving the yarn excellent antibacterial properties.
[0181] Therefore, the cool sunscreen yarn of the present invention can solve the problems of insufficient heat shielding performance of ordinary sunscreen yarns and poor heat dissipation performance of the human body. The use of PA6 fiber can also reduce the moisture absorption rate of the yarn and improve the quick-drying performance of the yarn; the use of PE fiber can further enhance the heat conduction effect. In addition, the yarn of the two-component chrysanthemum petal core process of the present invention can also be applied to functional fibers such as conductive, anti-static, electromagnetic shielding, heat insulation, and radiation resistance to achieve lateral and longitudinal two-way conduction.
[0182] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0183] The above embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for manufacturing a cool sunscreen yarn, characterized in that: Here are the steps: Zinc oxide particles are selected as the thermal conductive material, and the shape of the zinc oxide particles is flake and / or strip; the thickness of the flake zinc oxide is not less than 100 nanometers, the diameter D50 of the flake zinc oxide is greater than or equal to 500 nanometers and less than or equal to 1000 nanometers, and the diameter D97 of the flake zinc oxide is not more than 5000 nanometers; the diameter of the strip zinc oxide is greater than or equal to 100 nanometers and less than 300 nanometers, the length D50 of the strip zinc oxide is greater than or equal to 500 nanometers and less than or equal to 1000 nanometers, and the length D97 of the strip zinc oxide is not more than 5000 nanometers; Surface treatment of zinc oxide particles; Selecting shiny polyamide or polyethylene as fiber material, mixing it with zinc oxide particles, and preparing masterbatch containing zinc oxide; The prepared masterbatch is mixed with shiny polyamide chips or polyethylene chips and melt-spun to obtain yarn.
2. The method for manufacturing the cool sunscreen yarn according to claim 1, characterized in that: The surface treatment of zinc oxide particles comprises the following steps: Dissolve γ-aminopropyltriethoxysilane in acetone, and the mass of γ-aminopropyltriethoxysilane is 1% of the mass of zinc oxide; Add zinc oxide granules and stir at high speed; Heat to 100℃ and react for a while; Filter and separate the zinc oxide particles, and rinse them with anhydrous ethanol; The surface-treated zinc oxide particles were obtained by vacuum drying at 100°C.
3. The method for manufacturing the cool sunscreen yarn according to claim 2, characterized in that: The method of dissolving γ-aminopropyltriethoxysilane in acetone, wherein the mass of γ-aminopropyltriethoxysilane is 1% of the mass of zinc oxide, comprises the following steps: Weigh the mass of zinc oxide particles to be treated; Based on the 1% ratio, calculate the mass of γ-aminopropyltriethoxysilane required; The calculated γ-aminopropyltriethoxysilane was dissolved in an appropriate amount of acetone to form a solution.
4. The method for manufacturing the cool sunscreen yarn according to claim 1, characterized in that: The specific steps for preparing masterbatch are as follows: Dry the shiny polyamide slices or polyethylene slices in a vacuum environment at 80-100°C; Grind the slices thoroughly into powder; The sliced powder is mixed with the surface treated zinc oxide particles, a dispersant is added, and the mixture is stirred thoroughly; The mixed material is extruded and granulated to obtain a masterbatch.
5. The method for manufacturing the cool sunscreen yarn according to claim 4, characterized in that: The glossy polyamide slice or polyethylene slice is dried in a vacuum environment at 80-100° C., and the specific steps are: The polyamide slices were dried in a vacuum environment at 100 °C for 4 h; or, The polyethylene slices were dried in a vacuum environment at 80 °C for 2 h.
6. The method for manufacturing the cool sunscreen yarn according to claim 4, characterized in that: The specific steps of using the mixed material for extrusion granulation are as follows: The mixture of masterbatch and polyamide chips is extruded into pellets at 280°C by a twin-screw extruder; or, The mixture of masterbatch and polyethylene chips is extruded into granules at 220°C by a twin-screw extruder.
7. The method for manufacturing the cool sunscreen yarn according to claim 1, characterized in that: The melt spinning is a blending process, and the steps are: mixing the masterbatch and the fiber slices in a mass ratio of 6:94 to 10:90 and then melt spinning.
8. The method for manufacturing the cool sunscreen yarn according to claim 1, characterized in that: The melt spinning is preferably a two-component chrysanthemum petal core process, the steps are: The spinneret adopts a multi-hole spinneret to produce multi-daisy-petal core-shaped fibers. The two feed ports of the two components are respectively fed with fiber slices with different masterbatch contents, one of which is a fiber slice with a masterbatch addition of 10-30%, and the other is a fiber slice with a masterbatch addition of 0-10%. The two-component spinning unit is started, and the two fiber slices are melted and then spun into yarn through a porous daisy-petal core spinneret. The two fiber materials are spaced apart in the circumferential direction of the single fiber of the yarn, so that the cross-section of the fiber is distributed in the shape of a daisy-petal core, and several daisy petals with high-added masterbatch are connected at the core of the yarn.
9. A cool sun-proof yarn, characterized in that: The cool sun-protective yarn is made by the manufacturing method of any one of claims 1 to 8, and the melt spinning is a two-component chrysanthemum petal with core process, and the number of chrysanthemum petals is 8-24.
10. The cool sun-proof yarn according to claim 9, characterized in that: The cool sun-protective yarn comprises a yarn body, a plurality of first chrysanthemum petal areas and a plurality of second chrysanthemum petal areas are arranged at intervals along the circumference of the yarn body, a yarn central axis area is arranged in the center of the yarn body, and a plurality of the second chrysanthemum petal areas are connected through the yarn central axis area.